Reminder Design and Childhood Vaccination Coverage - Jonas Cuzulan Hirani; Miriam Wüst (Institute of Labor Economics (IZA), 2023)
A major policy concern across public vaccination programs is non-compliance. Exploiting Danish population data and three national reforms in regression discontinuity designs, we document the effects of reminders for childhood vaccination coverage. Retrospective reminders are primarily effective for families with small children and when sent out close to the recommended vaccination age. Digital and postal reminders are equally effective. Prospective reminders increase timely vaccinations in later childhood and help reaching high coverage for new vaccines in increasingly complex vaccination programs. While reminders prompt additional preventive care for focal children, we find no spillovers to other health behaviors or relatives.
Keywords: I1; I12; I18; 330; vaccination; child health; public policy; reminder; Denmark